THE EFFECTIVENESS OF EDUCATIONAL SUPERVISION IN PANDEMIC ERA COVID-19 - Siti Sanisah; Abdul Kadir; Lukman Lukman; Edi Edi (Jurnal Tatsqif, 2021)
This survey aims to determine the effectiveness of educational supervision in the era of the Covid-19 pandemic. The survey was conducted in two different locations/districts, namely in Central Lombok and East Lombok, involving 250 educators who were chosen randomly. The focus of the survey consists of three important aspects in educational supervision, namely the existence of supervision in schools, the level of attendance of supervisors and the usefulness of directions given by supervisors to educators and education staffs. The survey results concluded that supervision at schools was carried out internally and externally with varying levels of supervisor attendance to provide direction to educators and education staffs. The frequency of attendance of the internal supervisor (Principal) is considered more intense (71%) than other supervisors. Likewise, the directions given are considered more useful by 85% of respondents than the directions given by other supervisors. To maximize this, supervisors are expected to be able to work even more optimally and be able to provide constructive and relevant directions to the existing situation and conditions.